The Dynamics of The Boarding School Curriculum: A Study of Islamic Boarding Schools in Langkat District - OK, Azizah Hanum; Al-Farabi, Mohammad; Satifa, Julia (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This research aims to analyze the dynamics of the Islamic Boarding School curriculum in Langkat Regency, as well as the supporting and inhibiting factors for the curriculum, and evaluate it. The research is qualitative field research with a natural approach. The research employed data collection procedures through observation, interviews, and documentation studies. The findings indicate that: The Babussalam and Nuur Ar-Radhiyyah Modern Islamic Boarding Schools use a combination of the national curriculum (diknas) and the Islamic boarding school/Kuliyyatul Mu’allimin Al-Islamiyah (KMI) curriculum. The curriculum development process at these schools is influenced by several supporting and inhibiting factors. One of the inhibiting factors is: There is a natural selection process related to students’ enthusiasm and desire to learn. However, the media is still limited, and not all teachers follow independent curriculum guidance. The evaluation of curriculum development policies at the Babussalam and Nuur Ar-Radhiyyah Modern Islamic Boarding Schools has not yet been fully implemented. The incomplete availability of resources in each educational unit and the lack of a fully student-centered curriculum hinder optimal operation. Additionally, the facilities and infrastructure that can support implementation are not yet complete.